Effect of exposure to ambient particulate matter on risk of developing pulmonary tuberculosis: A systematic review and meta-analysis - Nisha Kumari; Shashi Bhushan Singh; Dewesh Kumar; Geetu Singh; Pravin Yannawar; Lakhan Majhee; Anjani Kumar; Nitika Keshri; Sandip Kumar; Sunil Kumar Mahto (Lung India, 2025)
Tuberculosis (TB) is a major global health challenge, particularly in polluted areas. The relationship between ambient particulate matter and TB risk remains unclear, making this systematic review and meta-analysis (SRMA) vital for assessing this link. This SRMA aimed to estimate the association between exposure to ambient particulate matter (PM10 and PM2.5) and the risk of pulmonary tuberculosis (PTB) infection. A literature search was conducted in PubMed, Web of Science, and Cochrane (English-language studies) on January 29, 2024. The review followed PRISMA Guidelines (2020) for comprehensive literature searches, data extraction, and quality assessment of included studies. A random-effects model was used for meta-analysis to estimate pooled effect sizes and assess heterogeneity. Study quality and publication bias were also evaluated. Of the 507 articles identified, 25 met the inclusion criteria. Long-term PM2.5 exposure was linked to a 26% increase in PTB risk (RR =1.26, 95% CI: 1.07–1.48), while short-term exposure raised the risk by 10% (RR =1.10, 95% CI: 0.98–1.25). Long-term PM10 exposure increased PTB risk by 7% (RR =1.07, 95% CI: 1.02–1.12), with short-term exposure showing a similar increase (RR =1.07, 95% CI: 0.95–1.17). Subgroup analysis revealed PTB risk increased by 15% in males and 29% in females for PM2.5, and by 10% in males and 7% in females for PM10. A 10 µg/m³ increase in Particulate matter is associated with a higher risk of pulmonary tuberculosis, highlighting the need for targeted public health measures to reduce particulate exposure, especially in high-risk urban and industrial areas.